Inhibition effect of glycyrrhiza polysaccharide (GCP) on tumor growth through regulation of the gut microbiota composition - Xiaoyu Zhang; Shuwu Zhao; Xinbo Song; Jianwei Jia; Zhaiyi Zhang; Huifang Zhou; Hui Fu; Huantian Cui; Shuo Hu; Minjie Fang; Xiaomin Liu; Yuhong Bian (Elsevier, 2018)
Glycyrrhiza Uralensis Polysaccharide (GCP), as a macromolecular polysaccharide extracted from the Traditional Chinese Medicine (TCM) - Licorice has been proved to inhibit tumor growth in vitro and in vivo; however, the specific anti-tumor mechanism of GCP needs to be further investigated. In this study, we explore the anti-tumor mechanism of GCP from the angle of gut microbiota. Colon carcinoma cells (CT-26) were used to set up a tumor-bearing mouse model. After 14 days of GCP treatment, the weights of tumors were significantly reduced. In addition, HE staining of tissue sections reflected that GCP could effectively inhibit tumor metastasis. 16SrRNA high-throughput sequencing of fecal samples showed a significant change between the model group and GCP group in the composition of gut microbiota. Subsequently, gut microbiota depletion and fecal transplantation experiments further confirmed the relationship between the anti-tumor effects of GCP and gut microbiota. Following depletion of gut microbiota, GCP cannot inhibit tumor growth. Fecal transplantation experiments found that transplanting the feces of GCP-treated mice, to a certain extent, could inhibit tumor growth and metastasis. These results indicate that Glycyrrhiza Polysaccharides exert anti-tumor effects by affecting gut microbiota composition. Keywords: Glycyrrhiza Uralensis Polysaccharides, Gut microbiota, Cancer, TCM, Anti-tumor